The Arab world unbound tapping into the power of 350 million consumers - Mahajan, Vijay, 1948- (Jossey-Bass, 2012)
"An expert's guide to exploring business opportunities in the burgeoning Arab marketplaceThis groundbreaking book reveals the myriad opportunities presented by the Arab World's market of 350 million consumers, who collectively wield the ninth-largest economy in the world. Based on the author's firsthand research, including hundreds of market visits and more than 600 interviews at companies doing business throughout the region, this book shows how globally interconnected and vibrant the Arab markets are. Through a rich blend of data and anecdotal observations, it chronicles how, by respecting the region's culture and religious norms, hundreds of local and multinational companies and entrepreneurs are creating successful businesses in this large and growing marketplace. Hundreds of interviews and illustrative examples peel away stereotypes about Arab consumers to reveal diverse, vibrant and entrepreneurial consumer markets Explains how multinational companies, such as Coca-Cola, Unilever, and Proctor & Gamble, and leading regional companies are working successfully in the Arab nations Shows how Arab entrepreneurs, both men and women, are shaping the regional and global marketplaces Vijay Mahajan, author of two previous award-winning books on emerging markets, is one of the world's most-cited researchers in the business and economics sector As the global marketplace continues to expand, this book offers anyone interested in investing in the Arab world an expert perspective on the boundless business opportunities"--